THE INFLUENCE OF STORE ATMOSPHERE, ISLAMIC SERVICE QUALITY, AND TASTE ON CONSUMER LOYALTY OF MIE GACOAN WITH CONSUMER SATISFACTION AS AN INTERVENING VARIABLE - Mangku Luhur, Richard Adam; Puspita, Rosana Eri (ULTIMA Management, 2025)
Abstract - This study examines the influence of store atmosphere, Islamic service quality, and taste on customer loyalty at Mie Gacoan Salatiga, with consumer satisfaction as a mediating variable. The culinary industry is growing rapidly in Indonesia, and Mie Gacoan has become a popular brand. In Salatiga, Mie Gacoan holds a 4.6-star rating based on 3,022 reviews despite some negative feedback. The research uses a quantitative approach with purposive sampling, involving 100 respondents from Salatiga. The findings show that store atmosphere and Islamic service quality do not significantly influence consumer loyalty, while taste has a positive and significant impact. Store atmosphere also does not significantly affect consumer satisfaction, whereas Islamic service quality and taste positively and significantly influence satisfaction. Furthermore, consumer satisfaction significantly affects loyalty and mediates the relationship between Islamic service quality and loyalty. However, it does not mediate the influence of store atmosphere or taste on loyalty. The results suggest that Islamic service quality and taste are key to improving consumer satisfaction. Satisfied consumers are more likely to recommend the product, which enhances consumer loyalty and drives business growth. Keywords: Store Atmosphere; Islamic Service Quality; Taste; Customer Satisfaction; Customer Loyalty.